Paracoccidioides brasiliensis 14-3-3 protein is important for virulence in a murine model - Marcos, Caroline Maria [UNESP]; de Oliveira, Haroldo Cesar [UNESP]; Assato, Patricia Akemi [UNESP]; de Andrade, Cleverton Roberto [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Oxford University Press (OUP), 2019)
The Paracoccidioides brasiliensis strain downregulated the expression of adhesin Pb14-3-3 (Pb14-3-3 aRNA) was evaluated in a murine model of paracoccidioidomycosis (PCM). Pb14-3-3 aRNA displays attenuated virulence and triggered the formation of fewer granulomas by lowering the fungal burden in the lungs. Additionally, the Pb14-3-3 aRNA showed more elongated yeast cells and less ability to induce pneumocytes apoptosis in vitro. Our results show that 14-3-3 is an important virulence factor in P. brasiliensis-induced pulmonary infection.
Keywords: Paracoccidioides brasiliensis: 14-3-3 protein; pneumocytes apoptosis; virulence in murine model